On a non-ideal global and local energy transfer, using an electro-magneto and magneto-rheological dampers - Balthazar, José Manoel [UNESP]; Palacios, Jorge L.F. [UNESP] (My University, 2010)
In this paper, we investigated the nonlinear vibrations of a Non-ideal (NIS) electromechanical absorber (NEVA), taking into account a modified mathematical model of (MR) Damper. We observed the presence of the Sommerfeld effect (it is the steady state frequencies of the DC motor, which it will usually increasing as more power (Voltage) is given to it, in a step-by-step fashion. When a resonance condition it is reached, the better part of this energy it is consumed to generate large amplitude vibrations of the foundation, without sensible change of the motor frequency). The obtained results, by using numerical and analytical simulations, were discussed, in details. Copyright © 2009 by ASME.